2020
DOI: 10.3201/eid2610.190804
|View full text |Cite
|
Sign up to set email alerts
|

Multicenter Prevalence Study Comparing Molecular and Toxin Assays for Clostridioides difficile Surveillance, Switzerland

Abstract: S ince its identification as a cause of antibiotic-associated pseudomembraneous colitis in 1978 (1), Clostridioides difficile has emerged as a major healthcare-associated pathogen worldwide. In the United States, C. difficile infection (CDI) rates doubled during 1996-2003 (2), and rates of CDI were reported to be 76.9 cases/10,000 discharges in 2005 (3). In a more recent national point-prevalence study including US healthcare facility in-patients, 13/1,000 patients were found to be either infected or colonized… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 22 publications
1
4
0
Order By: Relevance
“…We found an overall CDI incidence of 8.5% which is in line with the data reported in a previous metaanalysis [ 1 ]. Similarly to this study, we observed an increasing trend over time, which could be partially attributed to the enhanced sensitivity of molecular diagnostics now widely employed in most centers [ 3 ]. In our cohort, with an extensive surveillance after HCT, the majority of CDI cases (64.9%) were diagnosed during the post-engraftment period.…”
Section: To the Editorsupporting
confidence: 83%
See 1 more Smart Citation
“…We found an overall CDI incidence of 8.5% which is in line with the data reported in a previous metaanalysis [ 1 ]. Similarly to this study, we observed an increasing trend over time, which could be partially attributed to the enhanced sensitivity of molecular diagnostics now widely employed in most centers [ 3 ]. In our cohort, with an extensive surveillance after HCT, the majority of CDI cases (64.9%) were diagnosed during the post-engraftment period.…”
Section: To the Editorsupporting
confidence: 83%
“…Our findings showed that over 80% of patients had mild disease, consistent with previous studies in onco-hematological patients [ 7 ]. The lower prevalence of hypervirulent ribotypes in Switzerland, such as ribotype 027 [ 3 ], could contribute to this finding. Around 18% of patients in our cohort experienced CDI recurrence.…”
Section: To the Editormentioning
confidence: 99%
“…Diagnostic approaches have considerably evolved over the years [6,7]; the introduction and wide use of nucleic acid amplification tests (NAAT) offers great advantages, including high sensitivity and short turnaround times, but has raised concerns about the overdiagnosis of CDI [3][4][5]. In a nationwide multicenter pointprevalence study in Switzerland, the mean prevalence rate was 9.3 cases/10,000 patient bed-days when using a PCR detection method, and lower when using a two-stage enzyme immunoassay (EIA)-based algorithm (6.1 cases/10,000 patient bed-days) [8]. Despite the advancements in diagnostic methods, the optimal diagnostic algorithm remains debated, and strategies vary considerably between centers.…”
Section: Introductionmentioning
confidence: 99%
“…Despite the advancements in diagnostic methods, the optimal diagnostic algorithm remains debated, and strategies vary considerably between centers. A better appreciation of local diagnostic approaches is vital for evaluating CDI burden [8,9].…”
Section: Introductionmentioning
confidence: 99%
“…The cross-reactivity with other bacteria happened due to the presence of a constituent sugar of LPS. One recent method comparison study for C. difficile surveillance in Switzerland showed that, compared to the PCR method, enzyme immunoassay led to more falsenegative results of human stool samples [148]. Immunological methods usually require preenrichment to expose surface antigens, which leads to extended detection time.…”
Section: Immunology-based Methodsmentioning
confidence: 99%